PERAN HUTAN PANTAI DALAM MEREDUKSI TSUNAMI MENGGUNAKAN PEMODELAN COMCOT - Arnisti, Raissa Alimah; Rosalia, Ayang Armelita; Anzani, Luthfi; Harvan, Muhammad; Nurokhim, Arif; Sriyanto, Sesar Prabu Dwi (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
Panimbang sub-district is one of the areas affected by the tsunami in 2018, located directly opposite the Krakatau Volcano and close to the Sunda Strait subduction zone (megathrust), making it an area with a high threat of tsunami levels. This study aims to determine the impact of coastal forests in reducing tsunamis using COMCOT modeling as one of the mitigation efforts. The tsunami generator used uses the worst scenario earthquake that can occur in the Sunda Strait subduction zone area. The results show that the coastal forest in Panimbang sub-district with a width of 380 m can reduce the tsunami velocity by 50% compared to the coastal forest with a width of 30 m. In addition, the manning coefficient (n) value also has an influence in reducing the inundation area, inundation level height, and tsunami velocity.